Utilization of mandarin orange peel waste as source of bioactive compounds in stripped catfish feed formulation - ADI SUSANTO; AGUSTINA AGUSTINA; KOMSANAH SUKARTI; MAULINA AGRIANDINI; NURHALISA NURHALISA (Asian Journal of Agriculture, 2026)
Abstract. Susanto A, Agustina, Sukarti K, Agriandini M, Nurhalisa. 2026. Utilization of mandarin orange peel waste as source of bioactive compounds in stripped catfish feed formulation. Asian J Agric 10 (1): g100135. https://doi.org/10.13057/asianjagric/g100135. Mandarin orange peel contains bioactive compounds that can improve the health and growth of fish. The objective of this study is to analyze the bioactive compounds of mandarin orange peel to improve the health and growth of stripped catfish. Identification and determination of components of mandarin orange peel methanol extract used the LC-HRMS method. The study consisted of four treatments of orange peel powder with doses of 0, 2.5, 5.0, and 7.5 g kg-1 feed. In total, 180 fish weighing 9.08±0.31 g in groups of 15 fish were kept in plastic containers for 30 days and fed twice a day (to satiation) according to the treatments. The observed parameters were hematology (erythrocytes, hemoglobin, hematocrit, and leukocyte differential), growth performance, feed utilization, and survival rate. Results of LC-HRMS showed 1.285 bioactive compounds detected in orange peel, with the highest levels for Herniarin 9.962490% and D-Glucuronic Acid 9.935390%. Mandarin orange peel powder in the feed affected hematological parameters, growth performance, and feed utilization in stripped catfish (P<0.05). Hemoglobin, leukocyte, monocyte, and neutrophil parameters were higher in the treatment group compared to the control group. The findings revealed that 2.5 g kg-1 was the optimal dose because it produced the highest body weight, growth length, specific growth rate, feed utilization efficiency, and protein conversion ratio, with values ​​of 6.69 g, 12.57 cm, 1.79% per day, 74.67%, and 2.02%, respectively (P<0.05). The survival rate for all treatments reached 100%. This approach supports mandarin orange peel as a biological resource containing bioactive compounds, thus supporting its use as a sustainable feed additive for stripped catfish.